MENYEIMBANGKAN AUTOMASI DAN HUMANISASI: PERAN KEPEMIMPINAN VISIONER DALAM MENJAGA KESEJAHTERAAN PSIKOLOGIS KARYAWAN - Kartika Dyah Nurwiani; Fatkhur Rohman Albanjari (Dar El-Falah, 2026)
The digital transformation accelerated by generative artificial intelligence (GenAI) creates significant psychological pressures on employees, affecting not only productivity dimensions but also professional identity and job security. This study examines visionary leadership as a protective factor helping employees navigate automation-induced uncertainty, with psychological job security as a mediating variable toward psychological well-being. Drawing on Job Demands-Resources (JD-R) Theory, Self-Determination Theory (SDT), Human-Centered AI framework, and Industry 5.0 paradigm, this study proposes a conceptual model positioning visionary leadership (through AI sense-making, upskilling vision, empathy in technology, and human-centered AI orientation) as mechanisms shaping job security perceptions and psychological well-being. Data were collected from 203 employees across various sectors in Indonesia using 1 to 5 Likert scale instruments and analyzed via Structural Equation Modeling-Partial Least Squares (SEM-PLS) in SmartPLS 4. Results show visionary leadership (X) positively and significantly influences psychological job security (M) with path coefficient beta = 0.538 (t = 10.852, p < 0.001), and psychological job security influences psychological well-being (Y) with beta = 0.456 (t = 7.748, p < 0.001). The direct effect of visionary leadership on psychological well-being is also significant but smaller (beta = 0.233, t = 3.418, p < 0.01), while the indirect effect through mediation is beta = 0.245 (t = 6.177, p < 0.001), confirming partial mediation. These findings imply that visionary leadership alone is insufficient; it requires concrete upskilling policies and human-centered organizational culture to effectively protect employee psychological well-being in the AI era.